The Effect of Repeated Low-Level Red Light Versus 0.01% Atropine Treatment on Axial Length and Choroidal Parameters in Children with Myopia - Xuena Pang; Aicun Fu; Guangying Zheng; Weiqun Wang; Mei Zhong; Lili Shang; Minghang Chang; Xuemin Jin (Ophthalmology and Therapy)
Abstract Introduction This research was designed to compare the effectiveness of repeated low-level red light (RLRL) and 0.01% atropine on axial length (AL), spherical equivalent refraction (SER), and choroidal parameters in children with myopia. Methods We conducted a prospective, randomized, and single-blind controlled trial. Ninety-one children aged 6–12 years old were selected, with cycloplegic SER ≥ − 5.00 D and ≤ − 0.75 D. Participants were randomly assigned to the RLRL group and 0.01% atropine group. The primary outcomes included changes in AL, SER, and choroidal parameters after a duration of 6 months. Choroidal parameters specifically including the foveal, parafoveal, and perifoveal choroidal thickness (ChT) and the foveal, parafoveal, and perifoveal choroidal vessel volume (CVV). Results At 6-month follow-up, the AL and SER changes were − 0.09 mm (− 0.18, 0.01) compared to 0.13 mm (0.05, 0.24) (p < 0.001) and 0.25 D (0, 0.50) compared to − 0.25 D (− 0.53, 0) (p < 0.001) in the RLRL and 0.01% atropine groups. The foveal, parafoveal and perifoveal ChT changes were 36.38 µm (14.05, 65.39), 31.04 µm (4.09, 59.35), and 28.48 µm (5.35, 55.15), compared to 0.94 µm (− 9.20, 9.36), 3.52 µm (− 10.24, 14.45), and 6.14 µm (− 5.21, 15.69) (all p < 0.001) in the RLRL and 0.01% atropine groups. The foveal, parafoveal, and perifoveal CVV changes were 0.01 μm3 (0.00, 0.02), 0.05 μm3 (0.02, 0.09), and 0.20 μm3 (0.05, 0.30) compared to 0.00 μm3 (− 0.00, 0.01), 0.01 μm3 (− 0.02, 0.03), and 0.01 μm3 (− 0.06, 0.09) (p < 0.001) in the corresponding two groups. Conclusions After 6 months of treatment, RLRL was more effective than 0.01% atropine in controlling axial elongation and myopic progression among children with myopia. The foveal, parafoveal, and perifoveal ChT and foveal, parafoveal, and perifoveal CVV changes in the RLRL group were significantly higher than those in the 0.01% atropine group.